2015
DOI: 10.1016/j.physd.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Extreme phase sensitivity in systems with fractal isochrons

Abstract: Sensitivity to initial conditions is usually associated with chaotic dynamics and strange attractors. However, even systems with (quasi)periodic dynamics can exhibit it. In this context we report on the fractal properties of the isochrons of some continuous-time asymptotically periodic systems.We define a global measure of phase sensitivity that we call the phase sensitivity coefficient and show that it is an invariant of the system related to the capacity dimension of the isochrons. Similar results are also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…A close examination of the contour plots suggests that merging of trajectories indeed occur for certain initial conditions in (15). Additionally, the phase plots indicate that the kicking of the pendulum introduces a high level of phase sensitivity [5] close to the unstable periodic orbit.…”
Section: Point Spectrum Of the Operatormentioning
confidence: 83%
See 1 more Smart Citation
“…A close examination of the contour plots suggests that merging of trajectories indeed occur for certain initial conditions in (15). Additionally, the phase plots indicate that the kicking of the pendulum introduces a high level of phase sensitivity [5] close to the unstable periodic orbit.…”
Section: Point Spectrum Of the Operatormentioning
confidence: 83%
“…Clearly, if c is a bijection, the level sets of φ 0 separates the basins of every limit cycle. A method to find eigenfunctions directly from the time-histories of observables involves computing their infinite-time averages (5). These averages are projections of observables (6) onto the eigenspace at λ = 0, and for observables that are integrable on the set A 2 , these averages are well-defined almost everywhere in the kicked region (follows directly from theorem 1).…”
Section: Eigenspace Of Koopman At λ =mentioning
confidence: 99%
“…Figure 7 illustrates that the PTC for system (24) is indeed continuous. Panel (a) reproduces the PTC from Fig.…”
Section: Phase Resetting In the Fitzhugh-nagumo Modelmentioning
confidence: 93%
“…System (24) was presented and studied in [20], because experimental data on similar pacemaker cells suggested that the PTC was discontinuous; see already Fig. 6(a).…”
Section: Phase Resetting In the Fitzhugh-nagumo Modelmentioning
confidence: 99%
See 1 more Smart Citation